Upper Llandovery-Wenlock (Silurian) palynology of the Pentland Hills inliers Midland Valley of Scotland - Molyneux, S; Barron, H; Smith, R (2008)
The results of a palynological study on late Llandovery-Wenlock (mid-Silurian) successions in the North Esk, Bavelaw Castle and Loganlee inliers of the Pentland Hills, Midland Valley of Scotland, are documented. Palynological assemblages from the Reservoir Formation are dominated by acritarchs, but chitinozoa, cryptospores and scolecodonts are also present. Assemblages from the lower part of the Reservoir Formation are of low diversity and abundance, but marked increases in both abundance and diversity, particularly of the acritarchs, occur in the upper 200 m or so of the formation. The reasons for the marked increases are unclear, but could reflect changing environmental conditions during deposition of the upper Reservoir Formation, with the marine palynomorphs tracking changes in the location of certain physical and chemical properties of water-masses, for example nutrient availability, salinity or temperature. There is a general decline in the abundance and diversity of acritarchs and chitinozoans above the Reservoir Formation, although both groups, together with rare cryptospores, are present in samples from the Deerhope and Wether Law Linn formations. The Henshaw Formation yielded few marine microfossils, but more abundant and diverse spores and cyptospores than the underlying formations, consistent with an upward transition from marine to prograding terrestrial facies. The microfloras from the Reservoir, Deerhope and Wether Law Linn formations are consistent with the late Llandovery age indicated by graptolite evidence. A feature of assemblages from the Reservoir Formation, particularly the more productive samples from the upper part of the formation, is the common occurrence of sphaeromorph acritarchs, Moyeria cabottii and Tylotopalla species. The common occurrence of these forms gives the palynological assemblages a distinctive character. Similar sphaeromorph-Moyeria-Tylotopalla dominated acritarch microfloras occur at about the same level (spiralis Graptolite Biozone) in the Silurian succession of the Girvan Inlier, in the Drumyork Flags Formation. They might therefore be useful for correlating upper Llandovery rocks across the Midland Valley.